A Study on the Relationship between Self-Management and Quality of Life in End-Stage Renal Disease Patients Undergoing Hemodialysis - Fida' Husain; Ika Silvitasari; Nining Puji Astuti; Hafizh Budhi Irfano; Listiana Listiana (Poltekkes Kemenkes Aceh, 2025)
Background: End-Stage Renal Disease (ESRD) is a chronic disease that has a significant impact on patients' physical, psychological, and social functioning. While hemodialysis therapy prolongs life expectancy, it also places a significant physical and emotional burden. This condition can reduce their quality of life. Implementing good self-management behaviors, such as adherence to therapy, dietary adjustments, and emotional management, can help patients adapt and improve their well-being. Purpose: To identify the relationship between self-management and quality of life in ESRD patients undergoing hemodialysis in Surakarta. Methods: This study was a quantitative study with a cross-sectional design. The population consisted of 150 patients undergoing HD, and the sampling technique used convenience sampling with a sample size of 80 people. Inclusion criteria included patients undergoing HD for at least 6 months. The instrument used to measure self-management was the HemoDialysis Self-Management Instrument (HDSMI), while quality of life was measured using the Kidney Disease Quality of Life Short Form (KDQOL SF-36). The relationship between the two variables was analyzed using the Chi-square test. Results: This study found a significant positive relationship between self-management and quality of life in hemodialysis patients (p = 0.000; p < 0.05). Patients with good self-management skills tended to demonstrate higher levels of physical and psychological well-being. Conclusion: Improved self-management is positively associated with a higher quality of life in patients with end-stage renal disease undergoing hemodialysis. Therefore, nursing interventions should focus on strengthening self-management skills through health education and ongoing psychosocial support.